Increased response to prostaglandin H2 precedes changes in PGH synthase-1 expression in the SHR aorta. - Ge Tong; Vanhoutte Paul M; Boulanger Chantal M (Acta Pharmacologica Sinica; Vol 20, No 12 (December 1999): Acta Pharmacologica Sinica, 2016)
AIM: To determine the expression of PGH synthase-1 and the sensitivity of vascular smooth muscle to PGH2 in the aorta from the SHR at an age when no endothelium-dependent contractions to acetylcholine are observed under control conditions. METHODS: All experiments were performed in parallel on aortas from 20-wk-old SHR and Wistar-Kyoto normotensive rats (WKY). Rings, with or without endothelium, were suspended in conventional organ chambers for the recording of changes in isometric force. The expression of PGH synthase-1 was evaluated by reverse transcription-polymerase chain reaction (RT-PCR) and Western blot analysis. RESULTS: Under control conditions acetylcholine did not cause contractions of rings with or without endothelium. However, in the presence of nitro-L-arginine (NLA, an inhibitor of nitric-oxide synthase), it evoked endothelium-dependent contraction in the SHR but not in the WKY aortas. The expression of PGH synthase-1 was comparable in the aortas of both strains (with and without endothelium). PGH2 caused greater contractions in rings without endothelium from the SHR than those from WKY, while U46,619 evoked a comparable response, in aortas from both strains. CONCLUSION: In the aorta of 20-wk-old SHR, endothelium-dependent contractions to acetylcholine are observed only when the production of nitric oxide is prevented. They are associated with an augmented sensitivity of the smooth muscle to PGH2, but not with an increased expression of PGH synthase-1.